2022
DOI: 10.3389/fimmu.2022.972930
|View full text |Cite
|
Sign up to set email alerts
|

Application of recombinant antibodies for treatment of Clostridioides difficile infection: Current status and future perspective

Abstract: Clostridioides difficile (C. difficile), known as the major cause of antibiotic-associated diarrhea, is regarded as one of the most common healthcare-associated bacterial infections worldwide. Due to the emergence of hypervirulent strains, development of new therapeutic methods for C. difficile infection (CDI) has become crucially important. In this context, antibodies have been introduced as valuable tools in the research and clinical environments, as far as the effectiveness of antibody therapy for CDI was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 281 publications
0
16
0
Order By: Relevance
“…In contrast to monoclonal antibodies, protein scaffolds are single polypeptide chain structures without disulfide bridges or post-translational modifications that show high solubility and stability and can allow the selection for affinity, stability, and enzymatic activity ( Simeon and Chen, 2018 ; Gebauer and Skerra, 2020 ). Additionally, in vitro antibody display technologies have many advantages, including the ability to be genetically modified to increase selectivity, specificity, and sensitivity, ease of production in E. coli , and reproducibility ( Frenzel et al, 2017 ; Chiu et al, 2019 ; Raeisi et al, 2022a ). Hence, various studies have suggested the use of phage display-derived antibodies for diagnostic purposes ( Chamorro and Merkoçi, 2016 ; Mohd Ali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to monoclonal antibodies, protein scaffolds are single polypeptide chain structures without disulfide bridges or post-translational modifications that show high solubility and stability and can allow the selection for affinity, stability, and enzymatic activity ( Simeon and Chen, 2018 ; Gebauer and Skerra, 2020 ). Additionally, in vitro antibody display technologies have many advantages, including the ability to be genetically modified to increase selectivity, specificity, and sensitivity, ease of production in E. coli , and reproducibility ( Frenzel et al, 2017 ; Chiu et al, 2019 ; Raeisi et al, 2022a ). Hence, various studies have suggested the use of phage display-derived antibodies for diagnostic purposes ( Chamorro and Merkoçi, 2016 ; Mohd Ali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the hybridoma technology has been successful, it has many shortcomings, e.g., limited number of candidates, time-consuming, inefficiency to generate antibodies toward highly conserved antigens, self-antigens, sensitive antigens, and toxic antigens. A strategy that overcome the disadvantages of hybridoma is techniques based on in vitro antibody production, e.g., yeast display, ribosome display, phage display, and mammalian cell display methods ( Raeisi et al, 2022a ; Valldorf et al, 2022 ), which among them, phage display and ribosome display are preferred in most laboratories due to their large diversity in the range of 10 12 –10 15 variants with high transformation efficiency ( Kunamneni et al, 2020 ; Raeisi et al, 2022a ). Here, we discuss the rAb techniques that are currently being studied for diagnosis proposes.…”
Section: Applicable Formats Of Antibody For Detection Purposesmentioning
confidence: 99%
See 3 more Smart Citations